How is rehabilitation with and without an integrated self-management approach perceived by UK community-dwelling stroke survivors? A qualitative process evaluation to explore implementation and contextual variations. Issue 4 (3rd April 2017) - Jones, Fiona; McKevitt, Christopher; Riazi, Afsane; Liston, Matthew
Abstract : Objective: Self-management programmes could support long-term needs after stroke and using methods integrated into rehabilitation is one option. To explore theoretical assumptions and possible mechanisms of implementation a process evaluation was delivered alongside a cluster trial which has demonstrated feasibility of an integrated self-management programme (Bridges SMP) in community-dwelling stroke survivors. This paper aims to show the extent to which experiences from stroke survivors receiving rehabilitation in control (usual care) and intervention (integrated self-management) sites reflected the differences in rehabilitation received and whether their understandings aligned with the self-management approach employed. Design: Semistructured qualitative interviews carried out as part of a process evaluation analysed thematically. Setting: Study was based in South London; all interviews were carried out in participants' home setting. Participants: 22 stroke participants recruited; 12 from integrated self-management sites and 10 from usual care sites. Results: All participants revealed shared appreciation of knowledge and support from therapists but subtle differences emerged between sites in respect to perceptions about responsibility, control and how previous experiences were used. Accounts depicted a variance regarding who had structured and planned their rehabilitation, with greater flexibility about content and involvement perceived by participants from the integrated self-management sites. They also provided accounts and experiences which aligned with principles of the intervention, such as self-discovery and problem-solving. Conclusions: The findings reflect our theoretical assumptions and possible mechanisms of implementation that rehabilitation with a focus on supporting self-management is reflected in accounts and understandings of stroke survivors. Taken together with our previous research this justifies evaluating the effectiveness of Bridges SMP in a larger sample to further contribute to an understanding of the functioning of the intervention, implementation, contextual factors and mechanisms of impact. Trial registration number: ISRCTN42534180 ; Post-results.